Influence of Transporter Polymorphisms on Drug Disposition and Response: A Perspective From the International Transporter Consortium. Issue 5 (31st May 2018) - Yee, Sook Wah; Brackman, Deanna J.; Ennis, Elizabeth A.; Sugiyama, Yuichi; Kamdem, Landry K.; Blanchard, Rebecca; Galetin, Aleksandra; Zhang, Lei; Giacomini, Kathleen M.
Abstract : Advances in genomic technologies have led to a wealth of information identifying genetic polymorphisms in membrane transporters, specifically how these polymorphisms affect drug disposition and response. This review describes the current perspective of the International Transporter Consortium (ITC) on clinically important polymorphisms in membrane transporters. ITC suggests that, in addition to previously recommended polymorphisms in ABCG2 (BCRP) and SLCO1B1 (OATP1B1), polymorphisms in the emerging transporter, SLC22A1 (OCT1), be considered during drug development. Collectively, polymorphisms in these transporters are important determinants of interindividual differences in the levels, toxicities, and response to many drugs.